Patients and Methods of the PATH Biobank – A Resource for Breast Cancer Research - Waldmann, A.; Anzeneder, T.; Katalinic, A. (Geburtshilfe und Frauenheilkunde, 2014)
Introduction: The foundation PATH (Patientsʼ Tumour Bank of Hope) collects in a tumour bank samples of blood, tumour, and tumour-near normal tissue from breast cancer patients and supplements them systematically with health-care data. Material and Methods: For patients from the diagnosis years 2006–2009 quantitative data were evaluated with the help of mean values and standard deviations while for qualitative data absolute and relative incidences were assessed. Demographic and clinical features of women who used different numbers of information sources were tested for statistical significance by means of ANOVA and χ2 tests. The benchmark report of the WBC and two DMP reports were used to compare oncological care. Results: For research purposes tumour tissue samples are available for 59 % of the cases, normal tissue for 62 % and blood serum samples for 92 %. From 3573 women (diagnoses 2006–2009), a total of 2697 women (75.5 %) took part in follow-up. The characteristics of the follow-up patients did not relevantly differ from those of all the patients. The responsible physician was named as the most important source of information about the disease. Young women in particular consulted several sources and also used the internet to obtain information. Discussion: Compared with data on therapy from WBC and the DMP breast cancer in Bavaria or, respectively, North Rhineland reports, the PATH patients represent an only slightly selected sample. The PATH biobank is a (still) poorly used data and sample source, which is made available upon request and positive evaluation of the study protocol. Thus, it is possible to address current questions in a short time without having to undertake extensive recruiting procedures.
Keywords: breast; epidemiology; breast cancer